Do empowerments influence experiencing intimate partner violence (IPV)? A multi-continental study of women across low and lower-middle-income countries - M Z E M Naser Uddin Ahmed; MD. Nahid Hassan Nishan; Helene Dahlqvist; Saidur Rahman Mashreky; Koustuv Dalal (BMC Public Health)
Abstract Background Distinct regional variations are observed in terms of factors influencing intimate partner violence (IPV) when women are empowered. This is a noticeable gap, and no comprehensive studies explore these influencing factors across different continents. Therefore, this study aimed to assess the relationship between women’s empowerment, autonomy, and IPV across different continental regions. Method The Demographic and Health Survey (DHS) dataset across 26 countries with low and lower-middle-income countries was used in this study. We focused on a sample of 56,175 women aged 15–49 who had experienced IPV. For data analysis purposes, we have used the Chi-square test and binary logistic regression using Stata. We also account for complexities related to the survey and incorporate sampling weights. Results Among 56,175 women from all six continents, 22,236 experienced IPV. IPV prevalence varies across regions, ranging from 12.81% in Cambodia [95% CI: 11.75%-13.92%] to 69.61% in Sierra Leone [95% CI: 66.93%-72.18%], with an overall prevalence of 39.46%. Empowered women demonstrated reduced odds of experiencing IPV, with notable protective effects in regions like Sub-Saharan Africa (e.g., Burundi: OR: 0.36, 95% CI: 0.29–0.44) and South and Southeast Asia (e.g., Cambodia: OR: 0.38, 95% CI: 0.30–0.50), However, exceptions such as Nigeria (OR: 1.53, 95% CI: 1.30–1.79) underscore regional disparities in the impact of empowerment. Conclusions Empowering women socially through employment opportunities and autonomy significantly reduces the prevalence of IPV. Notably, women living below the poverty line and with limited education face heightened vulnerability. It is crucial for policymakers, organizations, and communities to utilize these findings to create more comprehensive environments for working women.